THE ROLE OF BELIEF MATHEMATICS ON STUDENTS' LEARNING OUTCOMES IN DIFFERENTIAL CALCULUS COURSES - Muhammad Arie Firmansyah; Lely Laillatus Syarifah (Universitas Muhammadiyah Tangerang, 2022)
The subjects in this study were second semester students of 2020/2021 mathematics education study program, Universitas Muhammadiyah Tangerang. The purpose of this study was to find out how big the role of mathematical belief in student learning outcomes in the differential calculus course which was held in the even semester of 2020/2021. The research method is a survey method with a descriptive correlation analysis technique with instruments in the form of questionnaires and tests. The data were analyzed by regression analysis using SPSS statistic 20 software. The results showed that based on the results of the analysis and discussion, conclusions could be drawn including the role of mathematical belief in giving a significant influence on student learning outcomes in the differential calculus course. The results of the study using SPSS 20 showed that the value of the close relationship between mathematical beliefs and learning outcomes was 0.89, this indicates that there is a very strong relationship between mathematical beliefs and learning outcomes. The results show that the belief in mathematics on the learning outcomes of the differential calculus course contributes 79.2%. Analysis of the Significance Test of the Role of Mathematics Belief on Learning Outcomes for Differential Calculus Courses shows that an increase in the mathematical belief score in the Differential Calculus course will give an increase of 0.830